The Impact of Project-Based Learning Using a STEM Approach on Developing Entrepreneurship Skills Among High School Female Students in Digital Technology (2-2) - Almoafa, Nuriyyah Naser Adullah (Journal of Curriculum and Teaching Methodology, 2024)
The current study aimed to identify the effect of project-based education according to the STEM approach in developing entrepreneurship skills among secondary school students in the subject of Digital Technology 2-2. To achieve this goal, the descriptive and quasi-experimental approaches were used, relying on the questionnaire as a study tool. The study community consisted of secondary school students at Secondary School 33 in Jeddah- Digital Technology 2-2 Tracks- in the Kingdom of Saudi Arabia. A random sample of (87) students was selected from the study community. The study concluded that project-based education according to the STEM curve has a very significant impact on developing entrepreneurship skills among secondary school students in the subject of Digital Technology (2-2) at a percentage of (85.3%), as it improves the skill of developing future plans and contributes to developing general plans for societal goals. The study presented a set of recommendations, the most important of which are: applying the project-based education method in teaching the Digital Technology (2-2) course and activating it in a correct scientific manner, and the need to pay attention to preparing training courses for teachers in designing and implementing educational units according to the STEM approach in entrepreneurship and providing them with the knowledge and skills necessary to achieve the goals of using STEM approach to education.
Keywords: Education; Project-Based Learning; Entrepreneurship; STEM Approach; Digital Technology 2-2